Zavedení ISMS v podniku - Pospíchal, Jindřich (Vysoké učení technické v Brně. Fakulta podnikatelská, 2016)
Diplomová práce je zaměřená na návrh zavedení systému řízení bezpečnosti informací ve firmě. Obsahuje základní teoretické poznatky a pojmy z bezpečnosti informačních systémů a popisuje normy ČSN ISO/IEC řady 27000. Na základě teoretické části a analýzy současného stavu je zpracován návrh ustanovení ISMS.

The master’s thesis is aimed at proposing an implementation of information security management system in a company. It covers basic theoretical background and concepts of information system security and describes standards of ČSN ISO/IEC 27000. Specific provisioning of ISMS is then proposed based on the theoretical background and analysis of current state.
Implementation of ISMS in a Company
Keywords: ISMS; ČSN ISO/IEC 27001; ČSN ISO/IEC 27002; bezpečnost informací; management bezpečnosti; návrh informační bezpečnosti; ISMS; ČSN ISO/IEC 27001; ČSN ISO/IEC 27002; information security; security management; information security design